Bone mass preservation with high-dose cholecalciferol and dietary calcium in HIV patients following antiretroviral therapy. Is it possible?. Issue 5 (3rd September 2018) - Mela, Quirico; Ruggiero, Valeria; Montaldo, Lorenza; Pisano, Umberto; Matta, Laura; Maria Pasetto, Cristina; Onali, Simona; Cacace, Enrico; Carta, Mauro Giovanni; Barca, Lucia; Chessa, Luchino
Abstract : Objective: To evaluate whether treatment with 100, 000 IU/month (equivalent to 3200 IU/day) of cholecalciferol and 1 g/day of dietary calcium supplementation in HIV patients following different cART regimens yields normal levels of vitamin D3 and PTH as well as whether changes in bone mineral density are clinically significant. Methods: Consecutive HIV patients following different cART regimens received 100, 000 IU/month (equivalent to 3200 IU/day) of cholecalciferol and 1 g/day of dietary calcium supplementation. The participants underwent BMD assessment via dual energy X-ray absorptiometry of the spine and hip at baseline (T0) and after 24 months (T1). Levels of 25(OH) vitamin D3 and parathyroid hormone (PTH) were assessed at T0 and T1. Quantitative variables were assessed with a paired t -test, independent t -test or analysis of variance, as appropriate. A chi-squared analysis was used to assess the association between qualitative variables. A p -value <0.05 was considered significant. Patients were divided into three groups depending on the cART regimen. Results: A total of 79 patients were included (40 males, 51% and 39 females, 49%), with a mean age of 46.6 (SD ±11.2) years, a baseline CD4 count of 649 cells/µl and a mean 25 hydroxycholecalciferol (25(OH) D3) value of 25 + 10 ng/ml. After 24 months, the 25(OH) D3 increased to 40 + 11 ng/ml. The initial BMDs at T0 were estimated as 0.919 (±0.27) and 0.867 (±0.14) g/cm 2 at the spine and hip, respectively. After 24 months, the BMD was 0.933 (±0.15) g/cm 2 at the spine and 0.857 (±0.14) g/cm 2 at the hip. Based on a BMD change exceeding 3%, a worsening was observed in 23% of patients at the spine and 27% at the hip, whereas stability or improvement was demonstrated in 77% of patients at the spine and 73% at the hip. Subgrouping patients based on antiretroviral therapy indicated that, at T1, there was a statistically significant increase in vitamin D3 concentration in all patients, while PTH concentration was not significantly reduced in patients taking tenofovir or efavirenz. BMD stability or improvement was demonstrated in 77% of patients at the spine and 73% at the hip after 24 months. The multivariate analysis confirms a decrease in vitamin D3 and an increase in PTH levels in smokers, as well higher vitamin D3 concentrations in males and lower spine BMDs in menopausal females. Conclusion: The proposed protocol of cholecalciferol and dietary calcium supplementation is safe and valid for correcting vitamin D abnormalities in almost all patients as well as reducing PTH levels in a high percentage of patients; however, it is not sufficient for normalization, particularly in patients exposed to tenofovir or efavirenz. At the spine, no significant BMD change was found in any of the therapy groups. At the hip, our data confirm a modest negative effect on bone mass caused by tenofovir and efavirenz.